2009
DOI: 10.1590/s0102-311x2009000600022
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados à morbidade respiratória entre 12 e 36 meses de vida de crianças nascidas de muito baixo peso oriundas de uma UTI neonatal pública

Abstract: O objetivo do estudo foi estimar a morbidade respiratória entre 12 e 36 meses em crianças prematuras e identificar os fatores associados. A população compreendeu 84 crianças de uma coorte de prematuros de muito baixo peso. O desfecho foi a taxa de incidência de morbidade respiratória. A associação entre as variáveis independentes e morbidade respiratória foi verificada por modelo linear generalizado. Entre 12 e 24 meses, 56,3% das crianças apresentaram morbidade respiratória. Entre 24 e 36 meses, 38,1% das cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 30 publications
3
7
0
3
Order By: Relevance
“…A prospective cohort study that analyzed morbidities related to prematurity (8) Data expressed in n (%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A prospective cohort study that analyzed morbidities related to prematurity (8) Data expressed in n (%).…”
Section: Discussionmentioning
confidence: 99%
“…term infants weighing less than 1,500 g and with gestational age of less than 34 weeks for 12 months of corrected age and revealed that only one baby died in the period (8) . Similar data were obtained in a Canadian study conducted in 2009 (6) , to monitor pre-term infants between 33 and 37 weeks for 12 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have also found that premature newborns that received mechanical ventilation (MV) during the neonatal period showed greater risk of developing respiratory diseases like asthma and pneumonia in early childhood when compared to those that did not receive MV 13,14,15,16,17 . Neonatal MV was also associated with altered pulmonary function (spirometry) at 8-9 years 18 , as well as increased odds of asthma during childhood and adulthood 19,20,21 .…”
Section: Introductionmentioning
confidence: 99%
“…Nesse sentido, o perfil epidemiológico aponta que as doenças respiratórias são o primeiro motivo de consulta em ambulatórios e serviços de urgência infantis, sendo a pneumonia e a diarreia as principais doenças em crianças menores de um ano (4) . Vale destacar que recém-nascidos prematuros são mais vulneráveis a desenvolver morbidades que os recém-nascidos a termo (7)(8) . Autores ainda apontam a condição socioeconômica, a exemplo baixa renda familiar e escolaridade materna, como fator diretamente relacionado às condições de saúde infantil (9) .…”
Section: Introductionunclassified